Desain dan Pembuatan Sistem Alat Monitoring Suhu Baterai Kendaraan Listrik Berbasis Internet Of Things (IoT) - Dwi Rama Hadi Prastyo; Mira Esculenta Martawati (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
In simplifying the process of monitoring the temperature of electric vehicle batteries, especially in discharging conditions, a remote electric vehicle battery temperature monitoring system was created. The problem with the previous monitoring system was that there was no electric battery temperature monitoring system, so users could not monitor the temperature condition of the vehicle battery when in use. The purpose of this study is to design an Internet of Things (IoT)-based electric vehicle battery temperature monitoring device system using the web and add a data logger to monitor battery temperature remotely and find out the difference in temperature values from the device with a thermogun. And the addition of a cut off feature when the battery overheats as one of the safety. The research method uses experiments, namely by comparing the speed between 30km/h and 50km/h and comparing the readings of the monitoring device with a thermogun. In proving the performance of the monitoring equipment, it is carried out with a distance of 1km, 2km, and 3km and in sloping road conditions. The data obtained were then analyzed using the paired T-test method. The results of the study showed that the tool worked quite well with the highest error value of 3.88%. And the battery temperature value between the speed of 30km/h and 50km/h is a significant difference with a P-value result of 0.035 which means that H0 is rejected and H1 is accepted.